2017
DOI: 10.1177/0972063417717894
|View full text |Cite
|
Sign up to set email alerts
|

A Baseline Study on Pattern of Helmet Use in the State of Rajasthan, India

Abstract: Head injuries sustained in the crash are the main cause of death and disability. Such deaths and disabilities can be prevented by consistent and correct wearing of a quality helmet. A baseline study was conducted to understand the pattern of helmet use in all 7 administrative divisional headquarters of state of Rajasthan in 2015. Among 1,17,553 two wheelers observed, almost two-fifth drivers (39.4%) wore helmet correctly, whereas, less than three-fifth (58.7%) did not. Almost equal percentage of male (58.6%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In a review of helmet use studies conducted Southeast Asian countries, Peltzer & Pengpid (2014) found that motorcycle helmet use varies widely within countries. Mathur, Gupta, and Bandhu (2017) found that helmet use can vary broadly even on a state level. The high variance in helmet use underscores the importance of conducting helmet use assessments at a number of observation sites within a given country.…”
Section: Factors Influencing Helmet Usementioning
confidence: 99%
“…In a review of helmet use studies conducted Southeast Asian countries, Peltzer & Pengpid (2014) found that motorcycle helmet use varies widely within countries. Mathur, Gupta, and Bandhu (2017) found that helmet use can vary broadly even on a state level. The high variance in helmet use underscores the importance of conducting helmet use assessments at a number of observation sites within a given country.…”
Section: Factors Influencing Helmet Usementioning
confidence: 99%
“…Thus, using standard, full-face, and properly strapped helmet termed as effective helmet use is key to reducing injuries and deaths to greatest extent in motorcycle crash. Previous road side observational studies examined the prevalence and factors associated with helmet use (any helmet or proper helmet use) but none of them specifically studied use of full-face and properly strapped helmet [ 9 , 13 15 ]. With this background, we assessed prevalence and factors associated with effective helmet use among the motorcyclists in Mysuru, a tier II city in Southern India.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 18 ] In the present study, 53.8% thought that pillion rider must wear helmet, but none of them followed it similar to a study done in Rajasthan by Mathur et al ., where 88% % of the passengers didn't wear helmet. [ 19 ] This shows that though most of the students had good awareness, they do not practice it and indicate wide knowledge–practice gap which needs attention to ensure road safety. About 81.8% of the participants thought that listening to music using earphones while driving bike is dangerous and only 4.6% used it.…”
Section: Discussionmentioning
confidence: 99%